If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -3(-5x + 8) = -88 Reorder the terms: -7x + -3(8 + -5x) = -88 -7x + (8 * -3 + -5x * -3) = -88 -7x + (-24 + 15x) = -88 Reorder the terms: -24 + -7x + 15x = -88 Combine like terms: -7x + 15x = 8x -24 + 8x = -88 Solving -24 + 8x = -88 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 8x = -88 + 24 Combine like terms: -24 + 24 = 0 0 + 8x = -88 + 24 8x = -88 + 24 Combine like terms: -88 + 24 = -64 8x = -64 Divide each side by '8'. x = -8 Simplifying x = -8
| 2(1/2) | | 5x^2+12x-1=0 | | 28-2x=6x | | 8^3/2 | | x+89=10x+8 | | 163-7x=29x+15 | | (x^3)/18 | | 9x+3=187 | | x^2+6x+8=24 | | (n+3)*6=72 | | S=C+x | | a/4+4=8 | | x^2-14x+4=0 | | 6x-12y-24=0 | | 14+14z=-8-6z | | Y=-.75x+4.5 | | 5(3-7a)=-230 | | 4x+9=99-6 | | Y=-.75x+18 | | 9a-4=68 | | 9x+16=9x+20 | | y=-15x^3+3x | | x^2-11x=8 | | x+2x=93 | | -3k-8=-2 | | 6n+5=-85-9n | | 2x^2-15-20=0 | | 3x+9=9x+99 | | 4(y-1)=y+13 | | 420/36=f/30 | | 4y+1=y+13 | | -56-3v=7-10v |